PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syahida Muftin, 12.05.52.0049; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the factors - factors that affect stock returns in manufacturing companies. The population in this study are all companies listed on the Indonesia Stock Exchange in 2011-2014.Â The sampling technique was done by purposive sampling. Based on the purposive sampling obtained a sample of 155 companies. Data analysis technique used is multiple linear regression analysis.Â The results showed that each variable has a different effect, namely ROA, PER provide positive and significant impact on stock returns, while DER and TATO provide negative and significant influence on stock returns, AG provide negative and not significant influence on stock returns, and CR provide positive and not significant influence on stock returns.Keywords: Return On Asset (ROA), Debt To Equity Ratio (DER), Price Earning Ratio (PER), Total Assets Turnover (TATO), Current Ratio (CR), Asset Growth (AG), Return Saham